STRATEGI PENGEMBANGAN BATIK SEBAGAI SALAH SATU ASET WISATA BELANJA DI KOTA PEKALONGAN - Roseika Solichin; Evi Yulia Purwanti (Universitas Diponegoro, 2013)
Setono Wholesale Market is a shopping tourism, which sells batik with wide range ofdistinctive motifs. From ancestral times up to now, the wholesale market is able to competewith other markets. From year to year, it has a growing number of visitors, and its revenuehas a significant impact on Pekalongan’s PAD.This research is achieving toward the development strategy of batik mass production onwhich should prioritized by batik entrepreneurs, due to strong competition nowadays.The analytical tools used in the research are SWOT (Strengths, Weaknesses/Limitations,Opportnities, and Threats) dan AHP (Analytical Hierarchy Process). Using variablesinclude the production, supply and place.Results of this study using SWOT and AHP analysis showed that Setono Wholesale Marketswell to every existing opportunities and threats. Conducting the batik festival can increasethe number of tourist visit to Pekalongan. Conducting national and international batikfestival as a solution for Pekalongan batik development having the value of 0.256 based ontourists respondent and value of 0.277 based on respondents with the consistency ratioabout 0.1, which means that the results are consistent. Proposed policy to conduct nationalbatik week (Pekan Batik Nasional/PBN) and international batik week (Pekan BatikInternasiional/PBI) is a solution with the highest priority. The batik festival can increasethe number of tourist visit to Pekalongan. The 5 leading priority according to keyinformans are: conducting national and international batik festivals, doing promotionthrough travel packages, establishing partnership with the private sector, conducting atraditional batik art performances and complementing infrastructure of batik tourism.